(untitled) (KULT_online, 2024)
In Bourdieu in the City: Challenging Urban Theory, Loïc Wacquant synthesizes Pierre Bourdieu’s topological sociology with the fundamental inquiries of urban studies, elucidating the potential synergies between the two domains. Progressing from a foundational exposition of Bourdieu’s theoretical framework to its applicability within the specific contexts of contemporary cities, Wacquant develops the neo-Bourdieusian approach within urban sociology. The book offers an innovative application of a classical theory, rendering it a valuable resource for urban research.